Proteomic profiling in incubation medium of mouse, rat and human precision‐cut liver slices for biomarker detection regarding acute drug‐induced liver injury. Issue 9 (30th August 2013) - van Swelm, Rachel P. L.; Hadi, Mackenzie; Laarakkers, Coby M. M.; Masereeuw, Rosalinde; Groothuis, Geny M. M.; Russel, Frans G. M.
ABSTRACT: Drug‐induced liver injury is one of the leading causes of drug withdrawal from the market. In this study, we investigated the applicability of protein profiling of the incubation medium of human, mouse and rat precision‐cut liver slices (PCLS) exposed to liver injury‐inducing drugs for biomarker identification, using matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry. PCLS were incubated with acetaminophen (APAP), 3‐acetamidophenol, diclofenac and lipopolysaccharide for 24–48 h. PCLS medium from all species treated with APAP demonstrated similar changes in protein profiles, as previously found in mouse urine after APAP‐induced liver injury, including the same key proteins: superoxide dismutase 1, carbonic anhydrase 3 and calmodulin. Further analysis showed that the concentration of hepcidin, a hepatic iron‐regulating hormone peptide, was reduced in PCLS medium after APAP treatment, resembling the decreased mouse plasma concentrations of hepcidin observed after APAP treatment. Interestingly, comparable results were obtained after 3‐acetamidophenol incubation in rat and human, but not mouse PCLS. Incubation with diclofenac, but not with lipopolysaccharide, resulted in the same toxicity parameters as observed for APAP, albeit to a lesser extent. In conclusion, proteomics can be applied to identify potential translational biomarkers using the PCLS system. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Drug‐induced liver injury often leads to drug withdrawal. Proteins released from human, mouse and rat precision‐cut liver slices (PCLS) exposed to several hepatotoxicants were profiled using MALDI‐TOF MS. Following acetaminophen treatment, similar changes in protein profiles (including the key proteins SOD1, CA3 and calmodulin) were demonstrated as previously found in vivo in mouse urine. Incubation with diclofenac resulted in the same toxicity parameters as observed for acetaminophen. In conclusion, proteomics can be applied to identify potential translational biomarkers in PCLS.